Effects of Podophyllum peltatum compounds in various preparations and dilutions on human neutrophil functions in vitro - Chirumbolo, S.; Conforti, A.; Lussignoli, S.; Metelmann, H.; Bellavite, P. (British Homeopathic Journal, 1997)
Human blood neutrophil granulocytes (neutrophils) treated with Podophyllum peltatum L.-derived compounds exhibited an enhanced oxidative response to subsequent challenge with bacterial formyl peptides. This priming effect was concerned with superoxide anion (O2−) release (respiratory burst). The phenomenon was observed with a potentized preparation containing, among other things, podophyllum extract (Podophyllum compositum), with Podophyllum 4x (final concentration of active principle about 0.025 μg/ml), whereas enhancement of O2− release was not caused by homoeopathic Podophyllum 12x or other components of the complex homoeopathic preparation. Purified podophyllotoxin had the same effect at doses of 0.1–10 μg/ml, whereas doses higher than 100 μg/ml of podophyllotoxin inhibited the respiratory burst, so that pure toxin showed a typical bi-phasic dose-response curve. Similar effects were obtained with purified colchicine (1–1000 μg/ml), a microtubule-disrupting agent. No priming by a Podophyllum-derived compound was observed on neutrophils stimulated with 50 ng/ml phorbol ester. Further, both potentized podophyllum-derived compounds and pure podophyllotoxin-inhibited cellular adhesion to the serum-coated surface of culture microplates. These results show that low potencies of a drug extract have specific stimulating effects on the activation of neutrophil metabolism. The same stimulating effects are also caused by low doses of the active principle of the drug, which is an inhibitor when used at high doses.
Keywords: Leukocyte function; Superoxide anion; Adhesion; Podophyllum peltatum L.; Podophyllotoxin; Colchicine; Hormesis